Virulence of 'Dickeya solani' and Dickeya dianthicola biovar‐1 and ‐7 strains on potato (Solanum tuberosum). (2nd August 2012) - Czajkowski, R.; de Boer, W. J.; van der Zouwen, P. S.; Kastelein, P.; Jafra, S.; de Haan, E. G.; van den Bovenkamp, G. W.; van der Wolf, J. M.
<x xml:space="preserve">Abstract</x> Studies were conducted to explain the relative success of 'Dickeya solani', a genetic clade of Dickeya biovar 3 and a blackleg‐causing organism that, after recent introduction, has spread rapidly in seed potato production in Europe to the extent that it is now more frequently detected than D. dianthicola. In vitro experiments showed that both species were motile, had comparable siderophore production and pectinolytic activity, and that there was no antagonism between them when growing. Both 'D. solani' and biovar 1 and biovar 7 of D. dianthicola rotted tuber tissue when inoculated at a low density of 103 CFU mL−1. In an agar overlay assay, D. dianthicola was susceptible to 80% of saprophytic bacteria isolated from tuber extracts, whereas 'D. solani' was susceptible to only 31%, suggesting that 'D. solani' could be a stronger competitor in the potato ecosystem. In greenhouse experiments at high temperatures (28°C), roots were more rapidly colonized by 'D. solani' than by biovar 1 or 7 of D. dianthicola and at 30 days after inoculation higher densities of 'D. solani' were found in stolons and progeny tubers. In co‐inoculated plants, fluorescent protein (GFP or DsRed)‐tagged 'D. solani' outcompeted D. dianthicola in plants grown from vacuum‐infiltrated tubers. In 3 years of field studies in the Netherlands with D. dianthicola and 'D. solani', disease incidence varied greatly annually and with strain. In summary, 'D. solani' possesses features which allow more efficient plant colonization than D. dianthicola at high temperatures. In temperate climates, however, tuber infections with 'D. solani' will not necessarily result in a higher disease incidence than infections with D. dianthicola, but latent seed infection could be more prevalent.